The Relevance Of Modern Cell Theory to The Verse Of The Qur’an About The Creation Of Living Creatures - Hasanah, Muqor Rama; Syarif, Ahmad; Fadillah, Noor (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Modern cell theory is the basis of biological understanding which states that cells are the structural and functional units of life, cell division underlies growth and reproduction, and each cell originates from the previous cell. This study aims to analyze the relevance of modern cell theory to the verses of the Qur'an regarding the creation of living things. The study was conducted in May - June 2025 at the Biology Education Study Program, Muhammadiyah University of Palangkaraya using qualitative methods and a literature study approach. Data were collected through a search of cell biology literature and interpretation of Qur'anic verses regarding the creation of living things. Data analysis was carried out by content analysis through data reduction, data presentation, and drawing conclusions. The results of the study indicate that the concept of cells as structural and functional units of life is in line with QS Al-Anbiya' [21]:30 about water as the basis of life, the concept of cell division (mitosis and meiosis) is in line with QS Al-Mu'minun [23]:13-14 about embryonic development, the concept of differentiation and cell specialization is relevant to QS Al-Alaq [96]:2 about the creation of humans from 'alaqah, and the concept of Omnis cellula e cellula is in line with QS Az-Zariyat [51]:49 about the creation of pairs. The conclusion of this study shows the integration of science and Islam that mutually strengthen the understanding of cell biology and the value of faith. This study is expected to be the basis for the development of Cell Biology teaching materials based on the integration of science and Islam to improve scientific literacy and the religious character of students.